Goal-directed modulation of the default network supports interactions between selective attention, working memory, and prior knowledge - Veronica Diveica; Roni Setton; Gary R. Turner; R. Nathan Spreng (Proceedings of the National Academy of Sciences, 2026)
Memory is central to flexible, goal-directed behavior. Prior knowledge shapes our current decisions and future plans and guides our attention to selectively prioritize relevant information in our complex, noisy world. Yet, most research on the neural basis of selective attention has focused on novel stimuli and has defined goal relevance based on perceptual features rather than prior knowledge. We investigated how the brain supports selective attention when goal relevance depends on prior knowledge, and compared selection of novel (memory-independent) versus familiar (memory-enhanced) stimuli. Using multiecho fMRI, we recorded brain activity during a selective working memory task involving pictures of famous (familiar) and anonymous (novel) people and places. We manipulated the relevance of fame to task performance: In “fame relevant” task blocks, participants selectively attended to famous while ignoring anonymous stimuli; in “fame irrelevant” blocks, they attended to anonymous while ignoring famous stimuli. Compared to a nonselective, categorization task, the selective working memory task elicited sustained coactivation of frontoparietal control and dorsal attention networks. Task-relevant contrasted with task-irrelevant stimuli elicited transient coactivation of frontoparietal control and default network regions, irrespective of stimulus fame. Within the DN, this effect was driven by both enhanced activation for task-relevant stimuli and suppression for task-irrelevant stimuli, confirming attention-driven neuromodulation. Further, selective working memory coactivated these high-order, heteromodal brain networks while lowering activity in visual regions. Our findings elucidate the neural underpinnings of prior knowledge-guided selection of perceptual inputs for working memory, suggesting differences from those previously reported for perception-guided selection.